2011
DOI: 10.1007/s00192-010-1353-4
|View full text |Cite
|
Sign up to set email alerts
|

Technique of anterior colporrhaphy: a Dutch evaluation

Abstract: Introduction and hypothesisTo evaluate the variation in techniques of anterior colporrhaphy among members of the Dutch Urogynecologic Society.MethodsA questionnaire evaluating the technique of anterior colporrhaphy, preoperative and postoperative care, and use of the POP-Q score was sent out by e-mail.ResultsOne hundred thirty-three completed questionnaires were received. The response rate was 65%. There are large variations in incisions, use of hydrodissection, method of plication, and excision of redundant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…This may be attributed to the large variation in surgical technique of anterior colporrhaphy, though other factors may play a role as well. 36 Compared with the RCT of Dietz et al 17 we found fewer anatomical recurrences of the apical compartment (3.4 versus 21%) after SSHP. The latter number is rather high for SSHP.…”
Section: Main Findingsmentioning
confidence: 47%
“…This may be attributed to the large variation in surgical technique of anterior colporrhaphy, though other factors may play a role as well. 36 Compared with the RCT of Dietz et al 17 we found fewer anatomical recurrences of the apical compartment (3.4 versus 21%) after SSHP. The latter number is rather high for SSHP.…”
Section: Main Findingsmentioning
confidence: 47%
“…Within the literature there are descriptions of different techniques, which are categorised under the umbrella term of 'anterior repair' [6][7][8][10][11][12][13][14][15][16]. As with previous questionnaire studies [3,6,8] this study identified that most surgeons dissect in a superficial plane and this was frequently combined with a midline repair of the vaginal muscularis. This technique was first described by Kelly in 1913 for the treatment of stress incontinence [10].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative methods (video observations and interviews) have allowed categorisation of the entire procedure. The degree of variation seen was greater than had previously been described in the literature when simple questionnaires were used [6][7][8]. The combination of these variable steps results in potentially hundreds of different types of native tissue anterior repair.…”
Section: Main Findingsmentioning
confidence: 93%
“…Typically, mesh is placed below the vaginal muscularis (fascia) directly against the rectum or bladder, as described by Muffly and Barber in 2010 [ 10 ]. The traditional plane of dissection is more superficial; the vaginal epithelium is split from the underlying muscularis to enable its plication [ 7 , 11 , 12 ]. Most surgeons in this study continue to use this technique and a past study of Dutch Urogynecologic Society members showed that almost half of the surgeons attempted to “dissect the vaginal mucosa as thin as possible from the bladder” (43%).…”
Section: Discussionmentioning
confidence: 99%